Emerging adult Filipinas’ impression of selected body positivity campaigns and its relationship with positive body image and purchasing decisions - Quitevis, Riva Iris S.
Clothing brands utilize body positivity campaigns in their marketing efforts to better appeal to their target market. Body positivity includes defining beauty broadly, filtering information in a body-protective manner, highlighting body assets, and minimizing perceived imperfections. These campaigns can give consumers different impressions and may impact their positive body image and purchasing decisions. This study explored the relationship between the impressions of selected emerging adult Filipinas of selected body positivity campaigns of local clothing brands to their positive body image and purchasing decisions. An online survey was conducted among 126 emerging adult Filipinas, yielding 51 valid responses. Participants aged 18 to 29 years were recruited through convenience and snowball sampling techniques. The gathered data were analyzed using descriptive statistics and Spearman rank correlation coefficient to examine relationships between variables. The results showed that emerging adult Filipinas generally have a positive impression of body positivity campaigns, specifically those that showcase diversity in physical abilities and those that align with their brand goals in promoting body positivity. There is a varying degree of positive and negative correlation between specific impressions of the selected emerging Filipinas to both their positive body image and likeliness of purchasing from local clothing brands with body positivity campaigns. However, some factors do not have a significant relationship with the variables. Further research on different life stages and between genders, using a more qualitative approach, is recommended to explore the topic in various demographics and reveal additional findings. Examining the brand’s perspective on body positivity campaigns may allow for a deeper understanding of how they translate their motivation for promoting body positivity into their campaign and brand goals.